2019
DOI: 10.3390/tropicalmed4040135
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Quantitative, Duplexed qPCR Assay for the Detection of Leishmania spp. Using Bisulphite Conversion Technology

Abstract: Leishmaniasis is caused by the flagellated protozoan Leishmania, and is a neglected tropical disease (NTD), as defined by the World Health Organisation (WHO). Bisulphite conversion technology converts all genomic material to a simplified form during the lysis step of the nucleic acid extraction process, and increases the efficiency of multiplex quantitative polymerase chain reaction (qPCR) reactions. Through utilization of qPCR real-time probes, in conjunction with bisulphite conversion, a new duplex assay tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Moreover, detection of multiple species distinctly and concurrently requires multiplex PCR assays, and designing a single PCR cycling protocol to suit each primer pair can present assay constraints. The use of the novel bisulphite-conversion technique can mitigate such limitations [ 124 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, detection of multiple species distinctly and concurrently requires multiplex PCR assays, and designing a single PCR cycling protocol to suit each primer pair can present assay constraints. The use of the novel bisulphite-conversion technique can mitigate such limitations [ 124 ].…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…The technique can give data on parasite load, which in turn provides information for prognosis and treatment, and is useful for epidemiological studies [ 186 , 187 ]. Bisulphite modification is a method for reducing the complexity of the genome prior to application of PCR that has been adapted to Leishmania detection in real-time PCR [ 124 , 188 ]. This assay achieved an analytical sensitivity of 10 genomic copies per real-time PCR reaction, and clinical sensitivity of 97.0% and specificity of 100.0%.…”
Section: Methods For the Detection And Diagnosis Of Leishmaniasismentioning
confidence: 99%
“…The targets commonly used for molecular diagnosis of Leishmania are directed to several regions of the ribosomal gene, such as the 18S rDNA, intergenic spacer sequences-ITS1 [16][17][18], conserved regions of the kDNA minicircles [19][20][21][22], and nuclear genes, such as the variable region of the hsp70 gene [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a pan- Leishmania assay can also be exploited in eco-epidemiological studies, including identification of vectors and reservoirs [ 24 ]. In recent years, only a few attempts to develop pan- Leishmania assays based on nucleic acids amplification (i.e., SL RNA, rDNA or kDNA minicircles) have been made [ 24 , 25 , 26 , 27 ]. We previously showed that qPCR-ML was able to detect Old World L. ( L .)…”
Section: Discussionmentioning
confidence: 99%